2019
DOI: 10.3389/fphys.2019.01345
|View full text |Cite
|
Sign up to set email alerts
|

An Unsettled Promise: The Newborn Piglet Model of Neonatal Acute Respiratory Distress Syndrome (NARDS). Physiologic Data and Systematic Review

Abstract: Despite great advances in mechanical ventilation and surfactant administration for the newborn infant with life-threatening respiratory failure no specific therapies are currently established to tackle major pro-inflammatory pathways. The susceptibility of the newborn infant with neonatal acute respiratory distress syndrome (NARDS) to exogenous surfactant is linked with a suppression of most of the immunologic responses by the innate immune system, however, additional corticosteroids applied in any severe pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 192 publications
0
8
0
Order By: Relevance
“…47 Pneumonia may be transmitted vertically from the mother or acquired from the postnatal environment, and the resultant inflammatory response leads to cellular injury that impairs gas exchange, alters pulmonary circulation, interferes with normal respiratory mechanics, denudates alveolar surfaces, and interferes with surfactant function, which results in respiratory failure leading to morbidity and mortality in newborn infants regardless of gestational age. 48 Respiratory distress syndrome primarily affects preterm infants, but RDS was also one of the leading causes in death of term infants in our study. It has been reported that the incidence of RDS increases in term infants with elective cesarean births, 49 and the reason for increased RDS in these infants is delayed removal of lung fluid and a lack of cortisol response associated with spontaneous labor.…”
Section: Discussionmentioning
confidence: 56%
“…47 Pneumonia may be transmitted vertically from the mother or acquired from the postnatal environment, and the resultant inflammatory response leads to cellular injury that impairs gas exchange, alters pulmonary circulation, interferes with normal respiratory mechanics, denudates alveolar surfaces, and interferes with surfactant function, which results in respiratory failure leading to morbidity and mortality in newborn infants regardless of gestational age. 48 Respiratory distress syndrome primarily affects preterm infants, but RDS was also one of the leading causes in death of term infants in our study. It has been reported that the incidence of RDS increases in term infants with elective cesarean births, 49 and the reason for increased RDS in these infants is delayed removal of lung fluid and a lack of cortisol response associated with spontaneous labor.…”
Section: Discussionmentioning
confidence: 56%
“…Swine tracheobronchical anatomy closely resembles humans grossly and histologically, making them ideal airway models 16–19 . We sought to determine the impact of a prolonged airway foreign body in the swine airway.…”
Section: Introductionmentioning
confidence: 99%
“…This could, however, be an advantage for neurodevelopment studies, since behavioral assessments can be performed from birth onward, in contrast to other models such as rats and dogs [ 28 ]. Regarding the respiratory system, there are some maturational differences ( Table 1 ), although respiratory disease models (meconium aspiration and lavage models, further discussed later in this review) have been developed in neonatal pigs [ 54 ]. Moreover, it is possible to reach the required degree of immaturity of the respiratory system in a pig model by using preterm or IUGR pigs.…”
Section: Anatomical Physiological and Developmental Similarities mentioning
confidence: 99%
“…Characteristics of lung function, immune response, hemodynamic during ventilation and renal function were described. The newborn pig has many similarities to the human newborn including lung development, the presence of lung macrophages, NO production, the response to lipopolysaccharides and the hypervariable region of toll like receptor 4 [ 54 , 68 , 181 ]. The latter neonatal acute lung injury model was also used for nonclinical studies of high frequency oscillatory ventilation and (partial) liquid ventilation using perfluorocarbons [ 182 , 183 ].…”
Section: Fields Of Applicationmentioning
confidence: 99%